2019
DOI: 10.1088/1757-899x/593/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Some important properties of strandboard manufactured from andong bamboo (Gigantochloa pseudoarundinacea)

Abstract: Andong bamboo (Gigantochloa pseudoarundinacea) is one of the most important bamboo species widely planted in West Java, Indonesia, and play a prominent role in the rural economy. The bottom and the middle parts of Andong bamboo culms are suitable for laminated bamboo lumber raw material. To improve the efficiency of bamboo utilization, the upper part of Andong bamboo culms were use as raw material for strandboard production. The objective of the study was to determine the effect of strand length and specific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
3
2
0
Order By: Relevance
“…The average IB values of the manufactured OSB ranged from 0.53 to 0.79 MPa (Table 5). This result was similar to those obtained for betung bamboo-based OSB (Febrianto et al 2012) and andong bamboo-based strand board (Sulastiningsih et al 2019). The comparable results from this study with andong-bamboo strand board from a previous study (Sulastiningsih et.al.…”
Section: Mechanical Properties the Internal Bond Strengthsupporting
confidence: 92%
See 2 more Smart Citations
“…The average IB values of the manufactured OSB ranged from 0.53 to 0.79 MPa (Table 5). This result was similar to those obtained for betung bamboo-based OSB (Febrianto et al 2012) and andong bamboo-based strand board (Sulastiningsih et al 2019). The comparable results from this study with andong-bamboo strand board from a previous study (Sulastiningsih et.al.…”
Section: Mechanical Properties the Internal Bond Strengthsupporting
confidence: 92%
“…The result obtained was very similar to the WA of andong bamboo-based strand board bonded with phenol-formaldehyde, which ranged from 22.8% to 29.6% (Sulastiningsih et al 2019); or the WA of moso bamboobased OSB bonded with MDI (which was 23.6%) at the targeted density of 0.73 g/cm 3 (Sumardi and Suzuki 2014). The comparable result with the andong-bamboo strand board reported by Sulastiningsih et. al.…”
Section: Water Absorptionsupporting
confidence: 83%
See 1 more Smart Citation
“…Generally, the higher moisture content will reduce the strength of the materials (Tsoumis 1991). Similar moisture content was found by Sulastiningsih et al (2019), which shows OSB made from Gigantochloa pseudoarundinaca with different strand lengths ranging from 9-9.7%. Another study by Sumardi et al (2022) showed that the MC of LBL zephyr and ply-bamboo zephyr were 11.74% and 11.63%, respectively.…”
Section: Moisture Contentsupporting
confidence: 79%
“…The topic of bamboo properties was the third most published paper. There were identified 26 papers covered the aspects of; properties and mechanical properties of several species of bamboo [85][86][87][88][89][90][91] as well as the properties of bamboo products as a building construction material [92][93][94][95][96][97]. The research on bamboo as an infrastructure material, namely; bridges [98,99], hardeners or foundation bases of roads [100][101][102], and walls for wave and water blocks [103][104][105] was also published.…”
Section: Themes and Topics Of Journalsmentioning
confidence: 99%